Model of language interpreter for medical tourism in Malaysia: a fuzzy Delphi approach - Samsudin, Aisyah Jahidah; Tg Abdul Rahman, Tg Ainul Farhah; Mohd Ali, Mohd Zamrus; Adam, Zalika; Isahak, Aishah; Nawi, Amani; Sahrir, Muhammad Sabri (Association Res Militaris, France, 2022)
Interpreter is one of the important individuals in connecting patients and hospital staffs. The role also contributes to the high enrollment of medical tourists to our country. Although there is a great need for language interpreters in medical institutions, there are only a limited number of language interpreters available for employment. Accordingly, a model of language and communication services for marketing medical tourism in Malaysia is required, in keeping with the MHTC's goal of making Malaysia the world's leading global healthcare destination. The purpose of this study is to establish a model of language interpreter for medical tourism, with the intention of boosting medical tourism to Malaysia as the world's leading healthcare destination. This study implemented qualitative method. The approach used to collect the data was using a questionnaire instrument that had been given to 8 experts. The criteria in the determination of experts are these experts consist of four fields: Arabic, English, communication, and tourism Malaysian lecturers who have served more than 10 years in public universities. All the data collected were analyzed using the Fuzzy Delphi method. The findings showed that there are three main components in preparing a competent medical interpreter which are language, communication, and medical tourism. The determination of the items for each component are based on the calculated threshold value (less than 0.2) and the percentage of the expert group (more than 75%). This study showed that there are three components of the interpreter model for medical tourism in Malaysia and only 21 out of 32 items are agreed by the lectures from four fields based on expert agreement.